Fixed points and self-reference - Raymond M. Smullyan (International Journal of Mathematics and Mathematical Sciences)
It is shown how Gödel's famous diagonal argument and a generalization of the recursion theorem are derivable from a common construation. The abstract fixed point theorem of this article is independent of both metamathematics and recursion theory and is perfectly comprehensible to the non-specialist.